Characteristics of the population served in a Cuban intensive care unit: study of the DINUCIs project - Julio González Aguilera; Yoleinis Esperanza Vázquez Belizón; Armando Arias Ortiz; Jorger Omar Cabrera Lavernia (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2020)
Background: The description of the general characteristics of patients treated in Intensive Care Units provides valuable information for the improvement of work in this service. Objective: to identify the characteristics and evolution of the patients admitted to an Intensive Care Unit. Methods: descriptive study, with data from the DINUCIs registry, from 2015 to 2017. 300 patients admitted for more than 24 hours, at the Carlos Manuel de Céspedes General University Hospital, in Bayamo were included. Some of the variables analyzed were hospital stay, mortality, APACHE II index, risk factors, infections and place of origin. Results: the mean age was 43.3 years. 52% belonged to the female sex. The average of APACHE II was 11.3 + 6.0, and the average stay was 6.8 days. Mortality was 11.0%. Hypoalbuminemia (14.6%), immunosuppression (11.0%) and diabetes mellitus (9.3%) represented the most frequent risk factors. 31.3% received a central venous catheter and 19.3% received artificial mechanical ventilation. 47.0% of the patients presented an infection on admission, and 7.2% one related to health care. Conclusion: The population in the Intensive Care Unit, in its majority, was in the middle age of life, belonged to the female sex and presented a surgical entity. Hypoalbuminemia, immunosuppression, and diabetes mellitus were expressed more frequently and with temporal variations. Community-acquired infections upon admission have a high incidence. Mortality increased according to severity.